A study on the relationship between work life culture and employees' satisfaction at Arabian Bay Resort, Bukit Gambang Resorts City / Nurshahirah Suhairi - Suhairi, Nurshahirah (Faculty of Business and Management, 2018)
Relationship between work life culture and employees' satisfaction was the titile of this research. The details in this chapter were research objective, research question,' research design and the result of this research. This research would be conduct at Arabian Bay Resort, Bukit Gambang Resort City. This research was conducted from September until December 2017. The total number of respondent in this research was 65 and the return number of questionnaire was 56. First chapter explain about the background of the study, statement problem, research objective, research question, research hypothesis significant of the study and the definition of terms. Chapter two chapter explains what is the dependent variable and independent variable for this research. There were four independent variable such as job sharing, childcare support, employees' welfare and wellness program. For dependent variable there was employees' satisfaction. Literature review explains what were the definitions, advantages and also the disadvantages of all the variable. For methodology, it consists 0,£ research design, sampling frame, the population at the place, sampling techniques, sample size, unit of analysis, data collection procedure, instrument, validity of instrument, reliability of instrument and the data analysis. Chapter four explain about the results and the finding of this research. After the respondent respond to the questionnaire what was the result of this research. This chapter explains what were the profile of respondent and analysis of findings. Last chapter in this research was chapter five that explain about the conclusion and recommendation for Arabian Bay Resort, Bukit Gambang Resort City and the for the future research.